Il lessico istituzionale della violenza contro le donne: modelli teorici a confronto - Daniela Bandelli (Culture e Studi del Sociale, 2017)
This article aims to clarify theoretical models underpinning some of the terms employed in institutional discourse on violence against women in Italy, namely ‘gender based violence’ (GBV), ‘domestic violence’ (DV), and ‘intimate partner violence’ (IPV). The first term qualifies disparate types of violence as consequences of gender inequality and sexism. Be- cause these factors are not always the principal or the sole causes of all cases of violence against women, the term should be used cautiously. DV and IPV categorize violent acts in light of the relationships between involved subjects and enable to reach either women and men in the role of aggressors and victims.